Psychological effects and physical symptoms among healthcare workers during first wave COVID-19 outbreak in Kangar, Perlis / Muhammad Afif Abd Rahman and Alia Azmi - Abd Rahman, Muhammad Afif; Azmi, Alia (Faculty of Health Sciences, Universiti Teknologi MARA, 2021)
Infectious disease outbreak is known to have a psychological impact on healthcare workers as well as the general population. With Malaysia now in a war against a global pandemic, the national healthcare system is on the verge of collapse, affecting not just the patients, but also the healthcare worker. As part of the effort to explore this issue, a retrospective cross-sectional study was conducted in Kangar District Health Office and Kangar Health Clinic to assess the psychological effects and physical symptoms of healthcare worker during COVID-19 outbreak. A survey on healthcare workers was conducted by a using self-administered questionnaire. The questionnaire was divided into four main sections; 1] demographic characteristic, 2] medical history, 3] symptom prevalence and 4] Depression Anxiety Stress Scale (DASS-21). Scoring system was used to assess Stress, Anxiety and Depression. The data was analyzed descriptively and using linear regression. Overall, the majority of the health care workers experienced normal psychological disturbance during this pandemic. All three physical symptoms (insomnia, headache and neck stiff) are also significantly associated with stress, anxiety and depression (p<0.01). While the reported COVID cases in Perlis have always been lower than national average, this study nevertheless recommends the provision for timely psychological support and interventions for healthcare workers who present with physical symptoms of stress and depression.